Taxonomic notes on the placement of Tibellus elongatus Tikader, 1960 and Apollophanes bangalores Tikader, 1963 (Araneae: Philodromidae) - Sudhin, Puthoor Pattammal; Sen, Souvik; Caleb, John T. D. (Zootaxa, 2022)
Tibellus elongatus Tikader, 1960 is redescribed, and the male is described for the first time. Examination of the types and newly collected specimens reveal that the species is misplaced in Tibellus and is hereby assigned to the genus Thanatus C. L. Koch, 1837—T. elongatus (Tikader, 1960) comb. nov. Another new combination is proposed: Lycopus bangalores (Tikader, 1963) comb. nov. (ex. Apollophanes).